DIGITAL INEQUALITIES AS A SOCIO-CULTURAL PROBLEM OF MODERN SOCIETY (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
Digital technologies have become an integral part of modern life, influencing all spheres of society. However, with the development of the digital era, new forms of inequality are emerging, called digital inequalities. This article explores digital inequalities as an important socio-cultural problem, analyzing their manifestations, causes and consequences. The article examines various aspects of digital inequalities, such as access to information technologies, skills in using digital tools, socio-cultural barriers and the impact on sociocultural dynamics of society. The article also suggests possible solutions to this problem, including educational programs, government support and initiatives to improve digital literacy. The purpose of the article is to realize the importance of solving digital inequalities in order to create a more just and inclusive society.
Keywords: digital inequalities, access, technology, education, digital literacy, socio-cultural barriers, economic factors, information technology, social isolation, development, infrastructure, sustainable development.